DNA barcoding shows taxonomic uncertainty in North Sumatran Mahseer, Neolissochilus: towards comprehensive revision in Indonesia - Larashati, Sekar; Wahyudewantoro, Gema; Widoretno, Mey Ristanti; Febrianti, Dwi; Marnis, Huria; Barus, Ternala Alexander; Sinuhaji, Yolanda Simaretha Christiany; Kusumah, Ruby Vidia; Samir, Octavianto; Widiyanto, Tri (Penerbit Universiti Kebangsaan Malaysia, 2025)
The mahseer species Neolissochilus holds significant ecological and socioeconomic value, but its wild population is declining. A major challenge in conservation efforts is taxonomy uncertainty. This study used DNA barcoding of three mitochondrial DNA (mtDNA) segments (COI, Cyt b, and 16S rRNA) to verify the morphological identification of nine specimens collected from Bonan Dolok River and eight Neolissochilus sumatranus from the Tulas River, as well as three Neolissochilus soro samples from the Tulas River, and eight from Boho River, respectively, in North Sumatera. Morphological identification was based on body height, eye diameter/length, length of pectoral fin to the dorsal fin, anal fin to the caudal fin, and dorsal fin branch rays. Neighbour Joining analysis was used to construct the phylogenetic trees, showing that samples of N. sumatranus and N. soro clustered with supported bootstrap values of 63-71%, and no genetic distance between them. ASAP and ABGD species delimitation supported this clustering. This suggests both are the same species and closely related to N. soroides and N. hendersoni (genetic distance: 0.001-0.012 and 0.000-0.002, respectively). This challenges existing taxonomy and emphasizes the need to revisit Neolissochilus classification in Indonesia. Further study involving traditional taxonomy and DNA barcoding on Neolissochilus species in Indonesia is needed to clarify species distinction, validate taxonomy, and update the conservation status. This approach will enhance species identification, guide conservation efforts, and improve management of these vital freshwater fish species.